Systematic Literatur Review : Media Pembelajaran Berbasis Audio Visual Di Sekolah Dasar - Elfara Puri Fauziah; Alda Rizki Amalia; Noor Mustaqim; Fina Fakhriya; Erik Aditia Ismaya (Student Scientific Creativity Journal, 2023)
Audio visual learning is a learning that refers to an image and sound, so the two components will be processed together to be presented in a presentation, show, and also the required program of events. This study aims to conduct a literature review related to audio-visual learning media in elementary schools. The research method used in this study is the SLR (Systematic Literature Review) method. Data collection is done by documenting all articles that have similar research on the intended topic. The articles used in this study were 10 national journal articles obtained from the Google Scholar database using the Harzing's Publish or Perish application. Based on this research, it was found that this audio-visual-based learning media is highly recommended for use by teachers in the learning process. This audio-visual-based learning media is feasible and very good for use in the learning process for elementary school children.